The Mythical as a Philosophical Method in Vergil’s Aeneid - KRAJINA, Filip; Perić, Zdravko (Anafora, 2023)
In this paper we discuss potential interpretations of Vergil's Aeneid from a philosophical perspective, which includes the Homeric, Stoical and Epicurean element, because the comparison of Homer's epics and Vergil’s Aeneid in the figuration of a literary text and philosophicity shows congruence. Platonic influence on Vergil, through Cicero and his eclectic philosophical approach, lies in the teaching of virtue. It is therefore essential to separate the ideas of the aforementioned philosophical systems in Vergil's epic and explain his mode of exposition by the mythical philosophical method. The plot and the causal and consequential links in the epic are controlled by God's Fate which is Stoically understood, meaning that the whole narrative structure is subordinated to the founding of Rome as an empire which God had intended to rule justly and well. Along with the ethical component, there is a relation with the ontological, because the philosophy of the Epicureans and the Stoics is characterized by the division of philosophy into ethics, logic and philosophy of nature. Aeneas’ model of characterization was not created according to the Stoic wise man ideal nor to the Epicurean, but the main role is that of a Homeric hero, as Aeneas still expresses emotions of anger and fury, as do most of the ancient heroes like Achilles and Odysseus, who, guided by emotional pain and grief owing to losing loved ones, became vengefully violent. The reason of such narrative motif is the idealization of emotional men in the Hellenistic period, as well as in the Roman period. Therefore, what was crucial in shaping the main character and his relationship towards the divine is the Roman culture and its ethical-ontological demands, which are manifested in religious form. The originator of the mythical philosophical method structured in epic poetry is Homer, whose latter influence establishes the principle for the formation of the epic. It is about the method of bringing out ideologized ethics, which is why it is cultural, and is formed by aestheticizing the mythological.